The Effect of Leadership Style and Work Motivation on Employee Performance: A Case Study of the PCC Department at PT. Adis Dimension Footwear - Firmansyah , Deri; Yulandari, Sri; Zakiah, Zakiah (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
This study aims to determine the effect of leadership style and work motivation on employee performance, both partially and simultaneously, at the PCC (Product Creation Center) Department of PT. Adis Dimension Footwear. The background of this research is based on indications of declining work effectiveness and motivation among team member-level employees in the PCC Department, which plays a vital role in the product development process. One of the phenomena that triggered this research is the demotivation experienced by team members due to a lack of support from their superiors, which also leads to a decline in performance. This research employs a quantitative method with an associative approach. Datawere collected through questionnaires distributed to 55 respondents, selected using the Slovin formula from a population of 120 employees. Data analysis included descriptive statistics, validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, t-test, F-test, multiple linear regression analysis, and coefficient of determination using SPSS version 26. Based on the research results show that leadership style has a significant effect on employee performance, work motivation also has a significant effect on employee performance and simultaneously, leadership style and work motivation have a significant effect on employee performance. These findings emphasize theimportance of applying effective leadership styles and improving work motivation to support optimal employee performance.